2022
DOI: 10.3389/fmicb.2022.899102
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gut Microbiome and Bile Acids in Primates With Diverse Diets

Abstract: Primates have evolved a variety of feeding habits and intestinal physiological structure. Gut microbiome act as metabolic organs in many biological processes and play a vital role in adaptation to dietary niches. Gut microbiome also convert primary bile acids (BAs) to secondary. BAs profile and gut microbiome are together influenced by diets and play a significant role in nutrient absorption. The regulation between gut microbiome and BAs metabolism is bidirectional although the relationship in primates consumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 74 publications
(135 reference statements)
1
6
0
Order By: Relevance
“…At the taxonomic level, Bacillota (utilize crude fibre) and Bacteroidetes (primary degraders of polysaccharides) were the most dominant bacteria in the gut microbiome of snub-nosed monkeys. Particularly, Bacillota with Lachnospiraceae and Ruminococcaceae families were the most abundant families in snub-nosed monkeys, a finding common to other studies on wild folivorous primates, possibly related to high-fibre consumption [100][101][102][103][104][105][106][107]. Microbes of the Lachnospiraceae and Ruminococcaceae families also contain enzyme transport mechanisms, and metabolic pathways that enable the degradation of complex plant material, such as cellulose, hemicellulose, and lignin.…”
Section: Adaptation To Folivorysupporting
confidence: 51%
See 1 more Smart Citation
“…At the taxonomic level, Bacillota (utilize crude fibre) and Bacteroidetes (primary degraders of polysaccharides) were the most dominant bacteria in the gut microbiome of snub-nosed monkeys. Particularly, Bacillota with Lachnospiraceae and Ruminococcaceae families were the most abundant families in snub-nosed monkeys, a finding common to other studies on wild folivorous primates, possibly related to high-fibre consumption [100][101][102][103][104][105][106][107]. Microbes of the Lachnospiraceae and Ruminococcaceae families also contain enzyme transport mechanisms, and metabolic pathways that enable the degradation of complex plant material, such as cellulose, hemicellulose, and lignin.…”
Section: Adaptation To Folivorysupporting
confidence: 51%
“…In addition to host-level genomic adaptations to folivory, the gut microbiome also plays a crucial role in snub-nosed monkeys. Previous studies have investigated the adaptation to folivory of snub-nosed monkeys at both the taxonomic and functional levels of the gut microbiome [11,[99][100][101][102][103][104][105][106][107]. At the taxonomic level, Bacillota (utilize crude fibre) and Bacteroidetes (primary degraders of polysaccharides) were the most dominant bacteria in the gut microbiome of snub-nosed monkeys.…”
Section: Adaptation To Folivorymentioning
confidence: 99%
“…Studies has suggested that the level of the secondary BAs was negatively related to Prevotella . [ 38 ] We also found the positive relationship between the Prevotella_sp900557255 and lithocholic acid. Besides, the lithocholic acid was positively related with Gemmiger_qucibialis , Bariatricus_comes , Faecalibacterium_prausnitzii_D , Blautia_A_obeum CAG_41_sp900066215 .…”
Section: Discussionmentioning
confidence: 55%
“…Tetracyclines are primarily excreted through the bile and can be reabsorbed in the intestine as a result of enterohepatic recirculation [ 111 ]. The gut microbiome can influence the composition of the bile, altering the concentration of tetracyclines and other compounds excreted in the bile [ 112 , 113 , 114 ]. Moreover, it has been suggested that alteration of the gut microbiome led to changes in bile acid composition, which in turn affected the expression of liver enzymes involved in tetracycline metabolism [ 112 ].…”
Section: How Can the Gut Microbiome Alter Tetracycline Treatment?mentioning
confidence: 99%